2020
DOI: 10.5614/j.eng.technol.sci.2020.52.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Septage Management in the Urban Areas of Indonesia – Case Study in Bandung City

Abstract: Because of the burgeoning urban population, there is huge pressure on both natural resources and basic urban infrastructure, especially sewerage systems, with Indonesia as no exception. It is estimated that about 95% of human waste in Indonesia ends up untreated or partially treated in septic tanks before being discharged in the natural environment, contaminating the living environment as well as adversely affecting human health and economic development. This study conducted a comprehensive investigation on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The critical point of a septic tank is regular desludging. Unfortunately, this is often ignored by users, resulting in sub-optimal performance (Bao et al 2020). Due to the lack of spaces in highly populated areas, septic tanks are often located close to shallow groundwater reservoir that is used as a clean water source (Harahap et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The critical point of a septic tank is regular desludging. Unfortunately, this is often ignored by users, resulting in sub-optimal performance (Bao et al 2020). Due to the lack of spaces in highly populated areas, septic tanks are often located close to shallow groundwater reservoir that is used as a clean water source (Harahap et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another problem that is often found in septic tanks is that 1) the effluent pipe is clogged with excreta due to, 2) the dimensions of the septic tank do not meet the requirements, 3) there are no ventilation pipes and access holes to drain the sludge, 4) the location of the effluent flow is too close to the influent, 5) there is no barrier between influent and effluent [6]. The problem of wastewater leakage from septic tanks and soil/groundwater pollution in Bandung City and Denpasar City septic tanks was that they have never been dislodged in the last 5 years [15]; construction design errors [16], as well as design errors in the construction of the septic tank manhole on collection pipes in communal WWTP system in Yogyakarta [17] and surface water pollution due to the effluent quality from an inadequate environmental sanitation system [18].…”
Section: Performance Evaluation and Problem Solvingmentioning
confidence: 99%
“…There were cases that desludging operators still dispose the collected faecal sludge not to Faecal Sludge Treatment Plant (FSTP) [5,6]. Moreover, Bao [7] who conducted research in Bandung City, found workers who neglected their safety by not using PPE and use poor conditioned desludging equipment. These unsafe practices certainly can potentially cause harm to the health and safety of the workers, the community and also the environment.…”
Section: Introductionmentioning
confidence: 99%